PEMBLOKIRAN REKENING OLEH PPATK: TINJAUAN KESEIMBANGAN ANTARA PERLINDUNGAN KEUANGAN DAN HAK ASASI MANUSIA - Farah, Ferlina (Faculty of Law, University of Muhammadiyaha Surabaya, 2025)
The blocking of accounts by the Financial Transaction Reports and Analysis Center (PPATK) is a crucial step in preventing money laundering and terrorism financing. While aimed at maintaining the integrity of the financial system, this practice is often carried out without a transparent legal process, potentially harming customers uninvolved in illegal activities. This article examines the dynamics between the preventive measures taken by PPATK and their implications for human rights. Using a qualitative approach, this study analyzes existing regulations and identifies gaps in the protection of individual rights. The findings indicate the need for better coordination between PPATK and the Financial Services Authority (OJK) and for strengthening regulations to ensure transparency in the account blocking process. Recommendations are also proposed to enhance the appeal mechanisms for affected customers